Multimode-coreless-multimode fiber biosensor based on surface plasmon resonance. (7th March 2019) - Lang, Tingting; Cao, Bobo; Shen, Changyu; Shi, Guohua
Abstract: This study presents a facile, rapid and effective method for the fabrication of optical fiber surface plasmon resonance biosensors. A section of coreless fiber is spliced between two multimode fibers to construct a multimode-coreless-multimode (MCM) fiber structure. We take full advantage of the transmission characteristics of the coreless fiber, and the experimental results confirm that this MCM after coating with a thin gold film is able to excite surface plasmon wave effectively. Three sensors with different lengths of coreless optical fibers of 1 cm, 1.6 cm and 2 cm were constructed. And when the refractive index (RI) of the sucrose solution changes from 1.33 to 1.3883, the RI sensitivity was measured to be 2129.66 nm/RIU, 2249.33 nm/RIU and 2307.93 nm/RIU, respectively. After a comprehensive comparison, we chose the MCM optical fiber sensor with a coreless fiber length of 1.6 cm for biological experiments. After directly immobilized the antibody on the gold film, the biosensor was able to selective detect human immunoglobulin G (HIgG) with a sensitivity of 215 nm/ (mg ml −1 ). The limit of detection is 0.465 µ g ml −1 . The biosensor exhibited effective antibody immobilization ability and high sensitivity for HIgG detection, which fully demonstrates its potential applications in the broader biomedical or chemical field.